Influence of Vitamin C on Hematology of Pangasianodon hypophthalmus (Sauvage, 1878) Juveniles during pre and post-challenge with Aeromonas hydrophila (Chester, 1901) - Daniel, N.; Muralidhar, A. P.; Srivastava, P. P.; Jain, K. K.; Prasad, K. Pani; Anandan, R.; Manish, J. (Fishery Technology, 2018)
A 60-day feeding trial was conducted to know the effect of vitamin C on the hematological responses of Pangasianodon hypophthalmus juveniles during pre- and post-challenge conditions with Aeromonas hydrophila. A total of seven purified diets were prepared with 0 (control), 17.5 (T1), 35 (T2), 70 (T3), 175 (T4), 350 (T5) and 700 (T6) mg ascorbic acid (AA) equivalent per kg of diet, supplied as Lascorbyl- 2-polyphosphate (LAPP) and fed to triplicate group of P. hypophthalmus juveniles (mean initial body weight: 3.23Â±0.01 g to 3.38Â±0.01 g) for 60 days twice daily. After the feeding and after challenging with A. hydrophila, the haematological parameters were measured in P. hypophthalmus juveniles. All haematological parameter values (except albumin-globulin ratio) viz., serum glucose, total protein, albumin, globulin, hemoglobin (Hb), total erythrocyte count (TEC), total white blood cells count (WBC), hematocrit value (HCT) increased significantly (p<0.05) in treatment groups than control (vitamin C depleted diet). Further, the increased hematological values for most of the parameters were observed in the range of 175 to 350 mg AA kg-1. Therefore, it is suggested that dietary supplementation of 175 to 350 mg AA kg-1 diet would be beneficial for the optimal hematological responses for P. hypophthalmus juveniles.